2016
DOI: 10.1136/bmj.i4162
|View full text |Cite
|
Sign up to set email alerts
|

What is the most effective treatment for frozen shoulder?

Abstract: What is the most effective treatment for frozen shoulder? professor of orthopaedic surgery reader in orthopaedics senior research fellow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 21 publications
1
44
1
4
Order By: Relevance
“…It is a general belief that frozen shoulder resolves spontaneously after 1-3 years, 9 although there is a paucity of long-term follow up data to support this. 10 symptoms, with 7-15% having some degree of permanent loss of movement. 6,11 On the basis of a study of patients with frozen shoulder with a mean follow-up of 4.4 years, only 59% of patients had normal or near-normal shoulders as defined by no or minimal symptoms.…”
Section: What Is the Natural History?mentioning
confidence: 99%
See 2 more Smart Citations
“…It is a general belief that frozen shoulder resolves spontaneously after 1-3 years, 9 although there is a paucity of long-term follow up data to support this. 10 symptoms, with 7-15% having some degree of permanent loss of movement. 6,11 On the basis of a study of patients with frozen shoulder with a mean follow-up of 4.4 years, only 59% of patients had normal or near-normal shoulders as defined by no or minimal symptoms.…”
Section: What Is the Natural History?mentioning
confidence: 99%
“…Many studies show benefit either alone or in conjunction with physiotherapy and/or a home-based exercise program. 8,10,21,22 Glenohumeral joint injection performed in the early stages of frozen shoulder by the primary care physician, with the necessary skills and equipment, can provide significant improvement in passive range of movement. 8,23 Figure 1 identifies the anatomical landmarks required to ensure the injection is located within the glenohumeral joint.…”
Section: Movement and Measuringmentioning
confidence: 99%
See 1 more Smart Citation
“…In this pathologic mechanism the capsule does not become adhered to the humerus, but the contracted capsule holds the humeral head tightly against the glenoid fossa, causing a progressive loss of the physiological movements (15). Based on this and on the absence of a significant correlation between joint space capacity and restricted ROM, some authors reported that tightness of capsule and soft tissues around bring to a proportional motion restriction, more in external rotation than internal rotation (38). Many authors divide the natural course of the disease in three stages (1)(2)(3)6,12,13,16,17): stage I (freezing or painful stage) of 3-9 months, characterized by pain and progressive reduction of function and joint mobility; stage II (frozen stage) of 4-12 months which may not lead to increased pain but to a strong limitation of movements and ROM particularly external rotation, frontal flexion and abduction; stage III (thawing stage) of 12-42 months characterized by a progressive rise and recovery of movements and ROM.…”
Section: Introductionmentioning
confidence: 99%
“…SIR, Frozen Shoulder is a remarkable example of a severe, yet self-limiting, inflammatory and fibrotic condition affecting the shoulder joint capsule. Patients experience pain and restricted shoulder joint motion for up to 3 years, severely limiting activities and disrupting quality of life [1]. The disease mechanisms are poorly understood and there are no truly effective therapies for symptomatic patients.…”
mentioning
confidence: 99%